Green Arms Race: Indonesia's Critical Minerals and its Sprint for Renewable Energy Sovereignty - Pasaribu, Naek Tua; Tama, Airlangga Aji; Azzari, Muhamad Kevin; Gautama, Ivan (Security Intelligence Terrorism Journal (SITJ), 2025)
The increasing global demand for renewable energy has pushed countries around the world to compete in acquiring critical minerals and developing green technology. This article aims to examine the policies, regulations, and incentives implemented by the Indonesian government to leverage its vast reserves of critical minerals such as nickel, tin, and rare earth elements. It also aims to compare Indonesia's approach with the strategies employed by major players like China and the United States. The analysis highlights Indonesia's strengths, including its mineral wealth and supportive policies, as well as challenges such as technological readiness and regulatory hurdles. The research aims to provide insights into how Indonesia can enhance its renewable energy capabilities and achieve energy sovereignty while navigating the complex geopolitical landscape by using SWOT and intelligence analysis. The results indicate that the Indonesian government must improve its efforts to maximize its own potential, including by maintaining the availability of mineral resources, establishing robust regulations, and providing incentives for developers in the renewable energy sector. Additionally, it is crucial to promptly address the issues that hinder Indonesia's progress in achieving renewable energy sovereignty, such as updating mineral reserve data, adapting technology and improving human resources, and enhancing oversight to prevent illegal smuggling of mineral resources for renewable energy.